2023
DOI: 10.1111/aos.15667
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐grader reliability in the Danish screening programme for diabetic retinopathy

Abstract: PurposeThe Danish Registry of Diabetic Retinopathy includes information from >200 000 patients who attends diabetic retinopathy (DR) screening in Denmark. Screening of patients with uncomplicated type 2 diabetes is often performed by practicing ophthalmologists, while patients with type 1 and complicated type 2 diabetes attends screening at hospitals. We performed a clinical reliability study of retinal images from Danish screening facilities to explore the inter‐grader agreement between the primary screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The screening in Denmark [ 2 , 42 ] is conducted by private practicing ophthalmologists and hospitals ensuring comprehensive coverage. A recent Danish study [ 62 ] revealed an impressive overall agreement of 93% between inter-grader reliability within the Danish screening program for DR. These results highlight the reliability and consistency of grading outcomes within the Danish screening program for DR.…”
Section: Discussionmentioning
confidence: 99%
“…The screening in Denmark [ 2 , 42 ] is conducted by private practicing ophthalmologists and hospitals ensuring comprehensive coverage. A recent Danish study [ 62 ] revealed an impressive overall agreement of 93% between inter-grader reliability within the Danish screening program for DR. These results highlight the reliability and consistency of grading outcomes within the Danish screening program for DR.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of DR is categorized using the International Clinical Diabetic Retinopathy Disease Severity Scale, which consists of five stages: level 0 (no DR), levels 1–3 (mild, moderate, and severe DR, respectively), and level 4 (proliferative DR) ( 13 ). DiaBase has recently been validated with high agreement between graders according to the severity of DR ( 14 ).…”
Section: Methodsmentioning
confidence: 99%